Designing and Implementing a COVID Language Resource Guide as a Response to an Acute Need. Issue 2 (3rd July 2021) - Altilio, Terry; Kelemen, Anne; Leff, Vickie
Abstract: The rise of COVID-19 in March, 2020 led to an urgent and acute need for communication guidelines to help clinicians facing a novel disease, amidst a cacophony of voices and demands, find the words to use in the face of this public health emergency. We identified critical topics that arose at the interface of staff, patient and family to guide the structure and content of a guideline. Organized in an easy to read table, the guide was made available to a wide variety of websites, organizations and schools as a free PDF resource across the country and beyond.